2010
DOI: 10.1128/jvi.00689-10
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Fitness of Oseltamivir-Sensitive and -Resistant Highly Pathogenic H5N1 Influenza Viruses in a Ferret Model

Abstract: The fitness of oseltamivir-resistant highly pathogenic H5N1 influenza viruses has important clinical implications. We generated recombinant human A/Vietnam/1203/04 (VN; clade 1) and A/Turkey/15/06 (TK; clade 2.2) influenza viruses containing the H274Y neuraminidase (NA) mutation, which confers resistance to NA inhibitors, and compared the fitness levels of the wild-type (WT) and resistant virus pairs in ferrets. The VN-H274Y and VN-WT viruses replicated to similar titers in the upper respiratory tract (URT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 49 publications
(63 reference statements)
2
30
0
Order By: Relevance
“…Mutations at Q136 have also been detected in ferrets infected with influenza A(H5N1). The Q136L variant was detected in the nasal wash of a zanamivir treated ferret infected with an A(H5N1) virus [28], while a Q136H mutation was detected in an A(H5N1) virus from a ferret not being treated with an antiviral [29]. These reports demonstrate that viruses with these mutations have the potential to infect or replicate in vivo both in the presence or absence of zanamivir pressure.…”
Section: Discussionmentioning
confidence: 76%
“…Mutations at Q136 have also been detected in ferrets infected with influenza A(H5N1). The Q136L variant was detected in the nasal wash of a zanamivir treated ferret infected with an A(H5N1) virus [28], while a Q136H mutation was detected in an A(H5N1) virus from a ferret not being treated with an antiviral [29]. These reports demonstrate that viruses with these mutations have the potential to infect or replicate in vivo both in the presence or absence of zanamivir pressure.…”
Section: Discussionmentioning
confidence: 76%
“…Recent studies in ferrets with 2 different strains of H275Y oseltamivir-resistant influenza A (H5N1) virus showed that they had different competitive fitness when compared with the wild-type virus. 23 The effect of various NAI-resistant mutations on the pathogenicity of a strain of H5N1 was also studied in ferrets. 24 Two of the NAI-resistant mutants were associated with higher viral titers and more inflammation in the lungs of animals than the wild-type virus.…”
Section: Oseltamivir Resistancementioning
confidence: 99%
“…A clone of this mutant H5N1 virus with the N294S substitution also had lower levels of virus replication and pathogenicity in mice and ferrets and less susceptibility to oseltamivir than did the wild-type virus [59]. In contrast, neither the H274Y nor the N294S NA mutations compromised the lethality or pathogenicity of clade 1 A/Vietnam/1203/2004 (H5N1) virus in mice and ferrets [7, 60, 61], suggesting that oseltamivir-resistant variants of H5N1 subtype may possess an undiminished phenotype and exhibit high pathogenicity in mammalian species. Interestingly, oseltamivir resistance mutations substantially decrease the enzymatic activity of avian-like NA glycoprotein of A/Vietnam/1203/2004 (H5N1) virus but do not affect virus pathogenicity in mice and ferrets [7, 60].…”
Section: Fitness Of Oseltamivir-resistant Highly Pathogenic Avian H5nmentioning
confidence: 99%
“…In contrast, neither the H274Y nor the N294S NA mutations compromised the lethality or pathogenicity of clade 1 A/Vietnam/1203/2004 (H5N1) virus in mice and ferrets [7, 60, 61], suggesting that oseltamivir-resistant variants of H5N1 subtype may possess an undiminished phenotype and exhibit high pathogenicity in mammalian species. Interestingly, oseltamivir resistance mutations substantially decrease the enzymatic activity of avian-like NA glycoprotein of A/Vietnam/1203/2004 (H5N1) virus but do not affect virus pathogenicity in mice and ferrets [7, 60]. Thus, the extremely efficient replication complexes of highly pathogenic H5N1 influenza viruses can overcome deficiency in NA function, leading to fitness similar to that of wild-type viruses.…”
Section: Fitness Of Oseltamivir-resistant Highly Pathogenic Avian H5nmentioning
confidence: 99%
See 1 more Smart Citation